2010
DOI: 10.4028/www.scientific.net/msf.638-642.3374
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Retained Austenite Stability on Mechanical Properties of 590MPa Grade TRIP Sheet Steels

Abstract: Industrial low alloy TRIP sheet steels contain blocky and lath-shaped retained austenite. In the present study, transformation behaviour of blocky and lath-shaped retained austenite during straining was investigated to clarify its effect on mechanical properties. Two types of TRIP steels containing almost the same amount but the different morphology of retained austenite were used. A steel containing large amount of lath-shaped retained austenite exhibits superior ductility, and sustains high work-hardenabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 9 publications
3
12
0
Order By: Relevance
“…All of the preceding observations correlate very well with those of Matsuda et al, [29] who showed similar transformation kinetic results for alloys in which the balance between lamellar and blocky RA was altered to favor lamellar RA, resulting in a more gradual overall RA to martensite transformation arising from the higher lamellar RA stability, a more sustained n incr curve, and overall improved properties. It should also be noted that, for a given heat treatment, the RA to martensite transformation was more gradual in the case of the 1.5Al alloy vs the 1.0Al-0.5Si alloy, consistent with the observations of Bellhouse and McDermid [17] for this alloy and of Samek et al [37] for alloys of similar composition.…”
Section: B Tensile Propertiessupporting
confidence: 78%
See 4 more Smart Citations
“…All of the preceding observations correlate very well with those of Matsuda et al, [29] who showed similar transformation kinetic results for alloys in which the balance between lamellar and blocky RA was altered to favor lamellar RA, resulting in a more gradual overall RA to martensite transformation arising from the higher lamellar RA stability, a more sustained n incr curve, and overall improved properties. It should also be noted that, for a given heat treatment, the RA to martensite transformation was more gradual in the case of the 1.5Al alloy vs the 1.0Al-0.5Si alloy, consistent with the observations of Bellhouse and McDermid [17] for this alloy and of Samek et al [37] for alloys of similar composition.…”
Section: B Tensile Propertiessupporting
confidence: 78%
“…This is consistent with the observations of some authors that lamellar RA has both higher chemical stability (due to its higher carbon content) and higher mechanical stability due to its low equivalent radius and the effect of being mechanically constrained by the surrounding phases, particularly the bainitic ferrite and martensite. [28,29,35,36] It should also be noted that the most gradual transformation kinetics, highest sustained n incr curves, and highest UTS 9 e u products were obtained for the 1.5Al 50 pct c120s alloy, where the ratio of blocky to lamellar RA (approximately 4) was lowest.…”
Section: B Tensile Propertiesmentioning
confidence: 91%
See 3 more Smart Citations